2019
DOI: 10.1128/msphere.00637-18
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Differences in HIV Inhibition by Different Interferon Alpha Subtypes While Having Overall Similar Biologic Effects

Abstract: Elucidating the functional role of the IFN-α subtypes is of particular importance for the development of efficacious therapies using exogenous IFN-α. Specifically, this will help define whether IFN therapy should be based on the use of pathogen-dependent IFN subtypes or, rather, IFN mutants with optimized IFNAR binding properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 40 publications
3
21
0
Order By: Relevance
“…Our data in Figs 1 and 2, as well as data from other studies [12][13][14][15], provide strong evidence for quantitative differences among the IFN-Is. To uncouple quantitative versus qualitative differences, we normalized our IFN-I treatments for ISRE-activity ( Fig 2B) for unbiased transcriptomics.…”
Section: Identification Of Novel Ifn-regulated Genes (Irgs) Based On supporting
confidence: 82%
See 4 more Smart Citations
“…Our data in Figs 1 and 2, as well as data from other studies [12][13][14][15], provide strong evidence for quantitative differences among the IFN-Is. To uncouple quantitative versus qualitative differences, we normalized our IFN-I treatments for ISRE-activity ( Fig 2B) for unbiased transcriptomics.…”
Section: Identification Of Novel Ifn-regulated Genes (Irgs) Based On supporting
confidence: 82%
“…Our group and others reported diverse antiviral potencies of the IFNα subtypes and IFNβ that correlated with their IFNAR binding properties. These data emphasize the contribution of quantitative differences in IFNAR signaling in controlling acute viral infection [12][13][14][15]76]. However, data from multiple in vivo studies also revealed that the IFNα subtypes may have Expression levels were based on TMM-transformed counts.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations